1981
DOI: 10.1203/00006450-198107000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diet in the Determination of Jejunal Sucrase Activity in the Weanling Rat

Abstract: SummaryThis study was designed to determine the critical difference between rat milk and rat chow with respect to their effects on jejunal sucrase activity during the fourth postnatal wk. Rats were weaned onto special diets on postnatal day 17, and jejunal sucrase was assayed on day 28. A pelleted diet containing lactose as sole carbohydrate did not cause depression of sucrase activity. Sucrase values (pmoles/hr/mg protein) were 10.49 k 0.81 (n = 15) for the lactose chow and 6.65 + 0.29 (n = 16) for the sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
5
21
0
Order By: Relevance
“…The fact that the small intestine of prolonged nursed rats shows similar development of maltase and sucrase activities at day 25 without eating a sucrose-and glucose-polymer-containing laboratory chow also suggests a basically preprogrammed control that cannot be overridden by diets at least of these two disaccharidases in their postnatal development. A similar increase in sucrase is also obsewed by Henning and Guerin (20) in nonweaned rats at day 28.…”
Section: Duodenal Segment Jejunal Segmentsupporting
confidence: 56%
“…The fact that the small intestine of prolonged nursed rats shows similar development of maltase and sucrase activities at day 25 without eating a sucrose-and glucose-polymer-containing laboratory chow also suggests a basically preprogrammed control that cannot be overridden by diets at least of these two disaccharidases in their postnatal development. A similar increase in sucrase is also obsewed by Henning and Guerin (20) in nonweaned rats at day 28.…”
Section: Duodenal Segment Jejunal Segmentsupporting
confidence: 56%
“…During the suckling period, luminal factors begin to stimulate immune cells present in the gut compartment, and this challenge is increased by solid diet ingestion that in rats begins spontaneously during the late suckling period (23). In humans, although intestinal IEL are present during gestation, stimulation by luminal factors clearly determines their number, which increases postnatally up to 10-fold by 1-2 year of age (24).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have identified qualitative and quantitative changes to the gastrointestinal tract following alterations in diet at this time. For example, weaning rats fed a diet low in carbohydrate but high in fat have a reduced expression of the brush-border enzyme sucrase, whereas the expression increases in those animals fed a diet high in carbohydrates but low in fat (Henning & Guerin, 1981). In lambs the transition from milk to grass results in a reduction in the concentration of monosaccharides in the lumen.…”
Section: Riboflavin Deficiency: Duodenum: Proliferation: Morphogenesismentioning
confidence: 99%